ANALISIS PERAN SEKTOR EKONOMI POTENSIAL TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI PROVINSI KALIMANTAN SELATAN - Dewi Maharani,; Khabib Musthafa, (Juremi: Jurnal Riset Ekonomi, 2024)
The research aims to evaluate the potential role of the economic sector in South Kalimantan Province. This quantitative research uses secondary data from the Central Statistics Agency (BPS). The study employs Location Quotient (LQ) analysis, Shift Share analysis, and Contribution analysis. The research results indicate that there are fourteen potential business sectors with an LQ value greater than 1 in South Kalimantan Province, but three other sectors that are not potential (mining and excavation, processing industry, and construction) cannot meet the needs of their region. Economic growth across South Kalimantan Province (Nij) is influenced by the growth of the business sector, which overall, based on the data in the table above, shows a value of Nij > 0, specifically 137,859,478,243 billion, meaning that all economic sectors in the economy of South Kalimantan Province are growing at a faster rate. In the shift-share analysis, the mining and excavation sector has a value of 90,014,977,449, the processing industry sector has a value of 13,281,588,187, and the wholesale and retail trade sector, including motor vehicle and motorcycle repair, has a value of 12,843,464,567. In the contribution analysis, there are three main sectors: mining and quarrying, agriculture, forestry and fishing, and the processing industry.